2016
DOI: 10.1002/cbdv.201600167
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light Microscopic Discovery of Up to 150 μm Long Helical Amyloid Fibrils Built of the Dodecapeptide H‐(Val‐Ala‐Leu)4‐OH and of Decapeptides Derived from Insulin

Abstract: In the formation of amyloid fibrils from small peptides, the appearance of superhelices of (P)- or (M)-helicity has been observed for the first time; high concentrations of the peptides and extended periods of incubation at physiological pH appear to be important for this phenomenon. In view of the general importance of peptide and protein aggregation, we give a brief overview with selected examples for demonstration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…No amplification of chirality was observed even after sonication or leaving the solutions to stand for prolonged times. In stark contrast with the previous porphyrin trimers [12][13][14][15] the amplification of chirality was even not observed after premixing stock solutions of 1a and 1b in good solvents such as CHCl 3 or PhCH 3 , followed by solvent removal and redissolution in heptane (Fig S11, ESI †). We concluded that monomer exchange is not thermodynamically favorable and the aggregation in non-solvents is kinetically controlled.…”
Section: Please Do Not Adjust Marginscontrasting
confidence: 77%
See 2 more Smart Citations
“…No amplification of chirality was observed even after sonication or leaving the solutions to stand for prolonged times. In stark contrast with the previous porphyrin trimers [12][13][14][15] the amplification of chirality was even not observed after premixing stock solutions of 1a and 1b in good solvents such as CHCl 3 or PhCH 3 , followed by solvent removal and redissolution in heptane (Fig S11, ESI †). We concluded that monomer exchange is not thermodynamically favorable and the aggregation in non-solvents is kinetically controlled.…”
Section: Please Do Not Adjust Marginscontrasting
confidence: 77%
“…Such spectral variations suggested self-assembly also at these low concentrations and were consistently observed upon replacing heptane with methylcyclohexane (MCH) (Fig S5, ESI †). The spectral variations appeared more attenuated compared to the previous porphyrin trimeric systems, [12][13][14][15] especially in terms of intensity drop and magnitude of the blue shift of the Soret band. Next, we investigated the self-assembly of chiral 1b with CD spectroscopy to assess the chiral amplification at 5 μM (Fig 2b).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 72%
See 1 more Smart Citation
“…Spectroscopic examination of the peptides containing cysteine residue in the C-terminal position showed, in all cases, shifting of the absorbance maximum on successive days during incubation (CR assay) [ 47 , 48 , 49 , 50 ]. However, characteristic lowering of the absorbance maximum over time was observed only in the cases of H– d Phe d Phe d Cys–OH ( 7- ent ) and H–TyrTyrCys–OH ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…These fragments, called hot spots, form amyloidogenic cores and can contain up to three or four amino acid residues. In vitro, these undergo aggregation, leading to amyloid-like structures [10,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%